Determining the Knowledge, Attitude and Practice of Mothers Regarding Neonatal Care at Department of Pediatrics Fatima Hospital, Baqai Medical University Karachi - Yasir Inam, Jalal Uddin Akbar, Syed Zafar Mehdi, Arshad Hamid Khan, Anwar Ul Haq, Saif Jalal, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The aim of this study was to assess the mother’s knowledge of neonatal care and their attitude towards existing preventive methods and practices. Materials and Methods: A hospital based Cross-Sectional descriptive Study was conducted on mothers who delivered recently in Fatima Hospital, Baqai Medical University and the mothers visiting with their neonate age of 28 days. Results: A total of 385 participants including the neonates of age 1 to 28 days were included in the study. We found statistically significant relationship between the mother’s age and the mother knowledge of neonatal care (P value = 0.002). Moreover, other factors that we found significantly conducive were the relationships between Illness and medication, mother’s age and breast feeding, mother’s education, and neonate vaccination (P value = 0.002). Conclusion: In this study, we observed that most of the mothers were unaware of neonatal care. Many of them were ignorant of the neonate vaccination and national immunization days. Most of them treated their sick neonates with traditional home remedies rather bringing them to the hospitals. A high proportion of mothers withheld breast feeding and top feeding during neonate illness. Their knowledge regarding infected umbilicus, neonate inactivity and lethargy was scarce. These findings indicate that there is a room of improvement in the current mother’s knowledge and practices of neonatal care. This study will facilitate the policy makers to design new care seeking practices that foster better knowledge of neonatal care among mothers. Keywords: Neonatal Care, immunization, breast feeding